Metodologia para seleção de ferramentas computacionais para o ensino de engenharia de tráfego - Martinez, Heloni Maura Martorano (Universidade Federal de São Carlos, 2006)
Computational tools - softwares become more and more useful in the scope of Engineering. Several authors have already confirmed its benefits for the engineering's students education. In the last years, the availability of specific softwares for Traffic Engineering have increased. Nowadays, the selection process to identify the more adjusted computational tool to each task is one of the major difficulties in its use. This paper presents a methodology for selecting computational tools - softwares to be used in teaching disciplines of Traffic Engineering. This methodology, named MESET - METHODOLOGY FOR SELECTING COMPUTATIONAL TOOLS FOR TEACHING TRAFFIC ENGINEERING, was based on United States Department of Transports method, (2004). Its original evaluation criteria and specific tasks were adapted for teaching use inside the Traffic Engineering s parameters from Brazilian reality. The component criteria and item were identified through research carried with Traffic Engineer s Brazilian universities teachers. After defining the adequate procedures and routines MESET was also demonstrated through the software Synchro/SimTraffic, demo version. Through the criteria adopted, MESET s application final results have indicated that the software Synchro is adjusted to teach the analysed item - the modeling of intersections traffic lights.
Keywords: Engenharia de tráfego; Engenharia - estudo e ensino; Software de aplicação; Ferramenta computacional - Synchro; Ferramenta computacional - Simtraffic; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES::ENGENHARIA DE TRAFEGO